PERSEPSI PELANGGAN TERHADAP KUALITAS PELAYANAN PUBLIK PERUSAHAAN LISTRIK NEGARA (PLN) UNIT PELAYANAN DAN JARINGAN (UPJ) BEKASI KOTA - Dessianyanthi, Dahlia; Hubeis, Aida Vitayala S. (Jurnal Penyuluhan, 2016)
Public service is one form of the state apparatus functions as a public servant as well as a servant of the state. Seeing an increasingly competitive business world today, the company that provide public service need to change their customer services into a profit center. The quality of service provides an important link between the company and customers, also can help to push the company to achieve their goals and give positive image. Company’s image depends on how the company give their services to the customer. Companies are required to constantly monitor public perceptions or opinions about the company, through its institutional functions of Public Relation (PR). The purpose of this research is to analyze the customer’s perception of the quality of public services at PLN UPJ Bekasi Kota, and the relationship between the internal and external factors with the customer’s perception of public services at PLN UPJ Bekasi Kota. The results of this research show the customer’s perception on the quality of public services at PLN UPJ Bekasi Kota is good with the average score equal to 3.86. Correlation test showed that there are five significant correlation, which is the relationship between education level and assurance, education level and responsiveness, education level and tangibles, income level and tangibles, and the frequency of respondents calling and responsiveness. Keywords: Public Service, Quality of Service, PLN